A merit parameter to determine the stacking order of heterogeneous diphasic soft armor systems. (1st June 2020) - Guo, Zherui; Chen, Weinong
Highlights: Performance of bi-material diphasic soft armor systems depends on stacking order. Existing studies and results depend highly on experiments and simulations. Cunniff velocity is good predictor of stacking order performance for two given materials. Additional experiments give further justification to this use of Cunniff velocity. Concept of "ballistically-thin" materials is discussed. Abstract: The effects of stacking order on the ballistic performance may be detrimental if the order is improperly chosen. When the frontal material is constrained transversely by the rear material, it results in sub-optimal performance compared to the alternate configuration where both layers can freely deform. In this study, we examine the possibility of using the Cunniff velocity as a merit parameter in determining the optimal stacking order of heterogeneous diphasic soft armor systems by reviewing the results from previous studies. Experiments were performed on heterogeneous systems comprising ballistic-grade polyurea, Twaron® fabric, and Dyneema® UD laminate plies. Results show that the two constituent materials should be ordered such that the material with a higher Cunniff velocity is placed at the rear to minimize interference. The use of the merit parameter is then analyzed via existing models to examine the effects of changing various parameters. We further discuss the idea of "ballistically-thin" materials in relation to the concept of membrane strain energy dissipation efficiency of a soft armor target.